O boicote digital e o consumo consciente em tempos de pandemia: o case da marca Madero - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The main objective of this research is to understand how consumers perceive and relate to the Madero brand, based on statements and opinions expressed through comments on social networks during the pandemic period. More than a case study, this analysis seeks to connect concepts from the area of consumption and understand - in a deeper way through the understanding of the data collected - how the consumer is organized in the digital environment to express and influence other people. To weave the basic knowledge of this new expressionism of the modern consumer, we will bring the main concepts of Cruz (2017), who understands what a boycott is, its origins, typifications and its validity in anti-brand narratives and actions. The object of study, which is the official page of the Madero brand on Facebook, expresses its relevance while it was the target of severe criticism in the year 2020, after controversial statements about the pandemic of the new Coronavirus made by the owner, Junior Durski. This scenario can be extensively explored so that we can understand greater notions, which encompass the entire universe of a brand, its intangible values and how the identification of consumers with such feelings is essential for its success. The work is built on theoretical-conceptual pillars of authors who have already developed knowledge on recurrent themes in research, such as Canclini (1997) approaches and their bias linked to citizenship, along with Barbosa (2006) and Campbell (2006) concepts; the living universe of the brand and its values with the contributions of Costa (2008) and Wheeler (2009); braiding themes with the concepts of boycott and consumer behavior, further developed by Friedman (1999) and Cruz (2017); as well as the new faces of the modern consumer, based on Kotler (2017) and Campbell (2006). With the bibliographic and conceptual support combined with the collection and preparation of data, it is possible to understand consumer feelings in the digital scenario, as well as their actions in the specific scope of the Madero brand. In addition, it will be possible to raise deeper notions about the behavior of brands in atypical periods of society, as seen today, and how this is a key part in communicating their intrinsic values.
Keywords: Consumo (Economia); Movimentos de protesto; COVID 19; Facebook (Rede social on-line); Madero; Consumption (Economy); Protest movements; CNPQ::CIENCIAS SOCIAIS APLICADAS